Consent gained from patients after breast surgery for the use of surplus tissue in research: an exploration. Issue 4 (30th March 2007) - Hamilton, S; Hepper, J; Hanby, A; Hewison, J
Abstract : Objectives: (1) To investigate the quality of consent gained for the use in research of tissue that is surplus after surgery. (2) To compare the use of two consent forms: a simple locally introduced form and a more complex centrally instigated form. (3) To discuss the attitudes of patients towards the use of their surplus tissue in research. Design: Data were collected through interviews and analysed with a combination of quantitative and qualitative analytical techniques. Participants and setting: Patients of the breast care unit at a teaching hospital were interviewed at home or in a quiet room at the hospital. Results: 57 people were interviewed out of 81 approached, between October 2003 and March 2004. Most participants had a poor level of knowledge about the consent they had given, but reported being happy about having given it. The patients who had signed the locally introduced form had considerably more knowledge than those who had signed the centrally instigated form (z = −2.56; p<0.05). Participants considered being well informed to be less important than believing that their opinions were valued and respected. Conclusions: The findings suggest that traditional models of informed consent are not universally applicable and, in this case, seem to overstate what people wish to know. The simple consent form achieved a better quality of informed consent and provided a better model of practice than the complex form, and it seemed that a focused approach to consent seeking is more effective and acceptable than more complex approaches.